Determination of Elements in Bone of Tuberculous arthritis Patients by Radioisotope X Ray Fluorescence Analysis - Başsarı, A.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Kluwer Academic Publishers, 1998)
The quantitative analysis of the human femoral bone of 17 tuberculosis-arthritis (Koch-arthritis) patients (9 males and 8 females) in the age range of 45–65, for Ca, P, Zn, Sr, Ba, La and Ce were performed by using radioisotope energy dispersive X-ray fluorescence (EDXRF) and the results were compared with those of 12 healthy control groups (8 males and 4 females) in the age range of 37–58. The results indicate that the concentrations of P, Ca, and Sr in the control group are higher than those in the patient group, while the concentrations of Zn, Ba, La and Ce are not significantly different.
Keywords: Physical Chemistry; Inorganic Chemistry; Quantitative Analysis; Patient Group; Healthy Control Group